Collocated Measurements of Light‐Absorbing Organic Carbon in PM2.5: Observation Uncertainty and Organic Tracer‐Based Source Apportionment. Issue 5 (4th March 2022) - Xie, Mingjie; Peng, Xiang; Shang, Yue; Yang, Li; Zhang, Yuanyuan; Wang, Yuhang; Liao, Hong
Abstract: In this study, collocated filter samples of particulate matter with aerodynamic diameter less than 2.5 μm (PM2.5 ) from northern Nanjing were extracted using water and methanol, followed by analysis of light absorption. A backup quartz filter was used to correct sampling artifacts caused by adsorption of gaseous organics. The collocated precision of light‐absorbing properties of water‐soluble organic carbon (WSOC) and methanol‐extractable organic carbon (MEOC) were parameterized using correlation coefficient ( r ), coefficient of divergence (COD), and average relative percent difference (ARPD, %). In general, the light absorption of WSOC and MEOC showed good agreement ( r  > 0.80, COD < 0.20) between collocated samples. Performing artifact correction is necessary and will increase the heterogeneity between collocated measurements. The duplicate‐derived ARPD values of MEOC absorption were more than 60% higher than those of WSOC absorption. Then, it would be inappropriate to assume a uniform uncertainty fraction (e.g., ∼10%) for WSOC and MEOC absorption in future studies on their climate effects and source apportionment. To apportion artifact‐corrected absorption of aerosol extracts to specific emission sources or formation pathways, positive matrix factorization was performed by using concentration data of selected bulk species and organic molecular markers. Among the nine identified factor/sources, the biomass burning factor had the highest average contributions to the absorption of both WSOC (31.6%) and MEOC (48.0%), followed by dust resuspension and coal combustion factors. Unlike combustion‐related primary emissions, the factors containing influences from atmospheric processing (e.g., secondary nitrate) contributed more fractions of WSOC absorption than MEOC absorption. Key Points: Collocated measurements provide an approach to estimate uncertainties in light‐absorbing properties of solvent‐extractable organic carbon Ignoring the adsorption of gaseous organics onto filter medium will lead to significant overestimation of brown carbon absorption Aerosol sources influenced by aging processes contributed more fractions of aqueous extracts absorption than methanol extracts absorption